Cannabis use and its association with psychopathological symptoms in a Swiss adult population: a cross-sectional analysis - Mosandl, Christoph Felix; Baltes-Flückiger, Lavinia; Kronschnabel, Jens; Meyer, Maximilian; Guessoum, Adrian; Herrmann, Oliver; Vogel, Marc; Walter, Marc; Pichler, Eva-Maria (Frontiers in Public Health, 2024)
Background As the most commonly used illicit substance, cannabis is gaining global acceptance through increasing legalization efforts. This shift intensifies the need for research to guide policymakers and healthcare providers in harm reduction and treatment strategies. Nonetheless, the relationship between psychopathological symptoms and cannabis use remains inadequately understood. Methods A sample of regular cannabis consumers completed self-reported assessments for depression (Patient Health Questionnaire-9), anxiety (General Anxiety Disorder-7), Attention-Deficit/Hyperactivity Disorder (ADHD; Adult ADHD Self-Report Scale V1.1), and psychosis (Early Recognition Inventory based on IRAOS) as well as previous black-market cannabis use patterns. Cannabis Use Disorder Identification Test Revised (CUDIT-R) was used to identify cannabis use disorder (CUD). To understand psychopathological symptom load related to cannabis consumption as well as cannabis use motives, multiple regression models were performed to identify psychopathological variables predicting cannabis use frequency and quantity. Linear regression and correlation analyses were conducted, adjusting for relevant covariates (age, gender, education, alcohol, other substance use). Results Three-hundred-sixty regular cannabis users interested in a study on regulated cannabis access in Basel, Switzerland were examined. In bivariate analysis, cannabis use frequency correlated with depressive (r(358) = 0.16, p = 0.003) and anxiety symptom load (r(358) = 0.11, p = 0.034). Cannabis quantity correlated with depressive (r(358) = 0.15, p = 0.005), ADHD (r(358) = 0.14, p = 0.008), and psychosis symptom load (r(358) = 0.16, p = 0.002). However, in the adjusted regression models only depressive and ADHD symptom loads were significantly associated with cannabis use frequency (p = 0.006 and p = 0.034, respectively) and quantity (p = 0.037 and p = 0.019, respectively). No significant correlations between cannabis consumption and anxiety or psychosis remained after adjustment. Conclusion ADHD and depressive symptoms correlate with increased cannabis use in a cohort of regular users, suggesting potential self-medication in nonclinical populations. With the rising availability of cannabis worldwide, these results highlight the necessity for longitudinal studies to disentangle the complex dynamics between cannabis consumption and mental health symptoms.